2023
DOI: 10.1002/fuce.202200098
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of graphite/polypropylene composite material reinforced by chopped carbon fibers for proton‐exchange membrane fuel cell bipolar plates

Abstract: In this work, chopped carbon fibers (CCFs) with different lengths were added to graphite/polypropylene (PP) composite materials to achieve high conductivity and flexural strength performances, which are required for use in proton exchange membrane fuel cells. The effects of CCF length (2-4 mm), CCF content (0-5 wt.%), graphite type-natural flake graphite (NFG) and synthetic graphite (SG), and graphite particle size (18-106 µm) on the graphite/PP/CCFs composites are examined. The conductivities of the composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…2 Bipolar plate performance needs and research directions at a glance. 36,37,[47][48][49][50][51][55][56][57][58][59][60][61][62][63][64][65][66][67] composite bipolar plates due to their small particle size, which gives them a high surface energy. In addition, because most of the carbon-based nanollers have poor compatibility with resins, [86][87][88] excessive addition of nanollers can not be wetted by resin.…”
Section: Application Of Nanofillers In Composite Bipolar Platesmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Bipolar plate performance needs and research directions at a glance. 36,37,[47][48][49][50][51][55][56][57][58][59][60][61][62][63][64][65][66][67] composite bipolar plates due to their small particle size, which gives them a high surface energy. In addition, because most of the carbon-based nanollers have poor compatibility with resins, [86][87][88] excessive addition of nanollers can not be wetted by resin.…”
Section: Application Of Nanofillers In Composite Bipolar Platesmentioning
confidence: 99%
“…As a kind of new type of bipolar plate with increased research heat in recent years, it combines the advantages of metal bipolar plate and graphite bipolar plate: easy to be processed, 54 good corrosion resistance, and low cost, 36,55,56 but due to the problems of poor compatibility between the resin and the graphite, the electrical conductivity and the mechanical properties are difficult to be balanced, and the porosity is large. In order to solve the problem of poor performance of composite bipolar plates, 57,58 the current primary use by adding conductive llers, such as carbon nanotubes (CNTs), 59,60 graphene, 60 carbon bers, [61][62][63] carbon black, [64][65][66][67] etc. Among these conductive llers, nanollers have become the main second conductive ller due to their excellent performance and signicant effect, oen used together with graphite to enhance the performance of composite bipolar plates.…”
Section: Introductionmentioning
confidence: 99%
“…Dhakate et al [12] developed expanded graphite-based nanocomposites by compression molding technique and obtained the samples with a packing density of 1.5-1.55 g/cm -3 . Compared with graphite resin-based composite (>12 GPa) plates, the Expanded graphite (3-8 GPa) composites have lower modulus values.Wei et al [13] prepared graphite/PP/CCFs composites using two different types of graphite powders as primary conductive fillers and PP as binder. The experimental results showed that the NFG-containing composites had higher electrical conductivity than the SG-containing composites for the same graphite particle size.…”
Section: Graphite/polymer Compositesmentioning
confidence: 99%
“…As an energy source for electric automobiles, PEMFC is advantageous because of its minimal emission of environmental pollutants and higher energy conversion rate. [12][13][14] Electric motors in fuel cell electric vehicles are operated by electricity produced from PEMFC. This system produces only water as a byproduct with high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Proton exchange membrane fuel cell (PEMFC) is a prominent fuel cell for applications in electric vehicles. As an energy source for electric automobiles, PEMFC is advantageous because of its minimal emission of environmental pollutants and higher energy conversion rate 12–14 . Electric motors in fuel cell electric vehicles are operated by electricity produced from PEMFC.…”
Section: Introductionmentioning
confidence: 99%